1995
DOI: 10.1177/026272809501500203
|View full text |Cite
|
Sign up to set email alerts
|

Panjabis in Britain: Cultural History and Cultural Choices

Abstract: Drawing on ethnographic research among the Panjabi diaspora, especially in Coventry, a British Midlands city, this paper argues for the significance of cultural interfaces, and of subjects' awareness of these, to the understanding of cultural transmission. Choices between cultural alternatives, from within and without the Panjabi repertoire, are apparent in subjects' reports of the changes they experience and the decisions they make. These are examined in association with five 'strands' of culture. In each cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…In their study on minority ethnic families, Beishon, Modood and Virdee, (1998) found that alongside popular activities such as sports and music lessons, some British Indian children engaged in Indian cultural activities such as learning Indian folk dance and languages which relate to their ethnic heritage. Others have shown that given the lack of provision within school curriculum, British Indian parents often seize upon opportunities such as language and religious history lessons offered by places of worship and community groups as a means for their children to foster positive ethnic group identities and garner an understanding of their ethnic background (Barn 2008;Beishon, Modood, and Virdee 1998;Nesbitt 1995). By identifying racial parenting ideologies vis-à-vis British Indian children's concerted cultivated through organised leisure, in this article we emphasise the need to look at race and class jointly in understanding educational strategies of parents.…”
Section: Concerted Cultivation As a Site Of Ethnic And Racial Sociali...mentioning
confidence: 99%
“…In their study on minority ethnic families, Beishon, Modood and Virdee, (1998) found that alongside popular activities such as sports and music lessons, some British Indian children engaged in Indian cultural activities such as learning Indian folk dance and languages which relate to their ethnic heritage. Others have shown that given the lack of provision within school curriculum, British Indian parents often seize upon opportunities such as language and religious history lessons offered by places of worship and community groups as a means for their children to foster positive ethnic group identities and garner an understanding of their ethnic background (Barn 2008;Beishon, Modood, and Virdee 1998;Nesbitt 1995). By identifying racial parenting ideologies vis-à-vis British Indian children's concerted cultivated through organised leisure, in this article we emphasise the need to look at race and class jointly in understanding educational strategies of parents.…”
Section: Concerted Cultivation As a Site Of Ethnic And Racial Sociali...mentioning
confidence: 99%